Review on the corrosion-promotion activity of graphene and its inhibition. (20th November 2021) - Sun, Wen; Yang, Yanjia; Yang, Zhengqing; Wang, Lida; Wang, Jing; Xu, Dake; Liu, Guichang
Highlights: Mechanism of the corrosion-promotion activity of graphene are summarized. Influencing factors of the corrosion-promotion activity of graphene are presented. Strategies for inhibiting corrosion-promotion activity of graphene are reviewed. Future development directions for corrosion protective graphene are proposed. Abstract: Graphene films (GFs) and graphene-reinforced nanocomposite coatings (GNCs) have received unprecedented attention for corrosion protection because graphene possesses a remarkable chemical inertness and is completely impermeable to aggressive chemicals. However, the high electric conductivity and positive potential of graphene make graphene-based metal protectors tend to exhibit an undesirable high corrosion-promotion activity (CPA), which is widely known as the phenomenon that graphene connecting with metal accelerates the corrosion of metal substrate by inducing micro-galvanic corrosion at the defect sites of GFs or GNCs in aggressive environments. Therefore, inhibiting the CPA of graphene is currently a key focus for the application of graphene in the field of corrosion protection. In this review, the mechanisms, influencing factors, and inhibition strategies of the CPA of GFs and GNCs are highlighted from the point of view of corrosion science to address the bottlenecks and challenges for future research and potential applications of graphene for corrosion protection.